Defining user requirements and strategies for a multimedia learning environment aimed at enhancing creativity in A' level design and technology teaching and learning - Ester Ehiyazaryan; Tim Lewis; Noel Williams (2004)
This paper describes preliminary research into establishing strategies for designing computerbased learning material, which have the potential to enhance creativity in post-16 design and technology (D&T) A’ level students. It explores meanings and perceptions of creativity from the point of view of D&T students. A series of three focus group interviews were carried out with A’ level students, in which aspects of creativity within the D&T classroom were discussed. The interviews provide insights into what students need from learning expressed in their own words. These insights are envisaged to provide an empirical basis for the future design and implementation of an interactive multimedia learning environment (IMLE), aimed at enhancing students’ creativity. The design and implementation of the learning environment will take place in the further stages of the wider research project, which identifying user requirements is a part of. The findings of the interviews form a list of user requirements to be used within an IMLE, concerning aspects of pedagogy and curriculum, or in terms of computer based learning, recommendations on the structuring of content and the structuring of learning interactions. Among the key findings are the need for, and importance of, collaborative work, discussing ideas and sharing perspectives, to developing and encouraging generative as well as evaluative thinking in students. The computer as a dialogue partner emerges as a valuable conceptual model within human computer interactions. The constructivist paradigm is seen as appropriate in supporting students’ natural learning strategy, experiential learning and the type of task-oriented, problem solving learning environment which would best support creative thinking in D&T. The findings discussed in this paper form the first part of a wider PhD research which explores the potential of multimedia technology and structured learning to enhancing creativity in D&T A’ level students. The stages of design and implementation of the learning environment are the next step of the research which will build directly on the findings of interview data discussed in this paper